1990
DOI: 10.2355/isijinternational.30.310
|View full text |Cite
|
Sign up to set email alerts
|

A formation mechanism of transverse cracks on CC slab surface.

Abstract: Some industrial measurewere summarizedto prevent both the segregation and the cracks to form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 0 publications
2
54
0
3
Order By: Relevance
“…In [15], the link between segregation, low ductility, oscillation mark formation and transverse cracking is clearly underlined. Mintz [23,24] realized a large review on hot ductility of steels and its relationship to the problem of transverse cracking in continuous casting.…”
Section: Fig 1: Sketch Of Continuous Casting Processmentioning
confidence: 99%
“…In [15], the link between segregation, low ductility, oscillation mark formation and transverse cracking is clearly underlined. Mintz [23,24] realized a large review on hot ductility of steels and its relationship to the problem of transverse cracking in continuous casting.…”
Section: Fig 1: Sketch Of Continuous Casting Processmentioning
confidence: 99%
“…However, Harada et al [16] have shown that transverse cracks are nonnally associated with very high segregation of phosphorous. Yashima et al [94] calculated that for a steel with 0.25 wt%C, the last liquid to solidify would contain about 5 wt%P.…”
Section: Influence Of Residual and Alloying Elementsmentioning
confidence: 99%
“…Harada et al [22] have shown that transverse surface cracks on continuously cast slabs have their origin in local segregation areas. They showed that a positive segregation of phosphorous can spread over an oscillation mark and, at the same time, a sharp negative segregation occurs adjacent to the positive segregation along the mark.…”
Section: Stresses and Strains In Continuous Castingmentioning
confidence: 99%
See 2 more Smart Citations